2015
DOI: 10.3389/fnhum.2015.00442
|View full text |Cite
|
Sign up to set email alerts
|

The neuroaesthetics of prose fiction: pitfalls, parameters and prospects

Abstract: There is a paucity of neuroaesthetic studies on prose fiction. This is in contrast to the very many impressive studies that have been conducted in recent times on the neuroaesthetics of sister arts such as painting, music and dance. Why might this be the case, what are its causes and, of greatest importance, how can it best be resolved? In this article, the pitfalls, parameters and prospects of a neuroaesthetics of prose fiction will be explored. The article itself is part critical review, part methodological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 96 publications
0
16
0
Order By: Relevance
“…In this respect, Lehne et al ( 2015 ) found that the rated amount of actions reported in story segments highly correlates with immersion ratings, suggesting that fiction feelings supported by scenes full of actions facilitate immersive processes (see also, Hsu et al, 2014 ; Lüdtke et al, 2014 ). Relating these findings to the field of visual aesthetics, it can be reasonably posited that, starting from posterior parietal/precuneus activation, specific processes are set (memory-, spatial-, and motor-related), which would allow the receiver (reader or art viewer) to be engaged in an immersive or, otherwise termed, transportation experience characterized by a full involvement of the recipient in a story (or image)—see also Burke ( 2015 ). These processes are hypothesized as part of an implicit system of embodied simulation, which is potentiated by the fact that, most of the time, the recipient is motionless when beholding an artwork or reading (“liberated embodied simulation”; see Wojciehowski and Gallese, 2011 ).…”
Section: Future Developments: a Link Between Visual Aesthetics And LImentioning
confidence: 99%
“…In this respect, Lehne et al ( 2015 ) found that the rated amount of actions reported in story segments highly correlates with immersion ratings, suggesting that fiction feelings supported by scenes full of actions facilitate immersive processes (see also, Hsu et al, 2014 ; Lüdtke et al, 2014 ). Relating these findings to the field of visual aesthetics, it can be reasonably posited that, starting from posterior parietal/precuneus activation, specific processes are set (memory-, spatial-, and motor-related), which would allow the receiver (reader or art viewer) to be engaged in an immersive or, otherwise termed, transportation experience characterized by a full involvement of the recipient in a story (or image)—see also Burke ( 2015 ). These processes are hypothesized as part of an implicit system of embodied simulation, which is potentiated by the fact that, most of the time, the recipient is motionless when beholding an artwork or reading (“liberated embodied simulation”; see Wojciehowski and Gallese, 2011 ).…”
Section: Future Developments: a Link Between Visual Aesthetics And LImentioning
confidence: 99%
“…Within the field of neurocognitive poetics (Jacobs, 2015a, 2016b; see also Burke, 2015) we are only beginning to understand the potential causes and effects of ludic reading. One line of theorizing trying to explain what motivates readers to pass time with written stories or poems highlights the role of immersion .…”
Section: Liking Words and Ludic Readingmentioning
confidence: 99%
“…Therefore, when discussing the recognition reaction of the subjects, the recognition reaction time of the subjects when they make the unrecognizable judgment will be converted to 5000ms. Meanwhile, the reaction time when the subjects make the unrecognizable judgment is reserved, which is used to study the processing time of the subjects when they make the unrecognizable judgment (Burke, 2015). Matched with the beauty, clarity and content availability of art works, altogether 18 experimental conditions are constituted.…”
Section: Resultsmentioning
confidence: 99%